Food production potential and environmental sustainability of different integrated farming system models in northwest India - Fatima, Ayesha; Singh, Vinod Kumar; Babu, Subhash; Singh, Rajiv Kumar; Upadhyay, Pravin Kumar; Rathore, Sanjay Singh; Kumar, Basant; Hasanain, Mohammad; Parween, Hena (Frontiers in Sustainable Food Systems, 2023)
Accelerated energy use, negative environmental outcomes, and poor economic returns questioned the sustainability of contemporary agricultural production systems globally. The task is much more daunting in the northwestern part of India where the over exploitation of natural resources is a major concern for sustainable agricultural planning. An integrated farming system (IFS) encompasses various enterprises such as crops, dairy, poultry, and fisheries can offer a myriad of benefits in terms of enhanced farm productivity, profitability, and environmental sustainability. Hence, the study hypothesized that the complementary interaction between the different enterprises would improve food production and reduce negative environmental outcomes. Therefore, production potential and environmental sustainability in terms of energy efficiency, greenhouse gas emissions, and eco-efficiency of nine IFS models, namely, crop enterprise (M2); crop + dairy (M3); crop + dairy + fishery (M4); crop + dairy + fishery + poultry (M5); crop + dairy + fishery + poultry + duckery (M6); crop + dairy + fishery + poultry + duckery + apiary (M7); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation (M8); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit (M9); crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit + vermicompost (M10), were compared with the rice–wheat system (M1; the existing system). All the IFS models were tested between 2018 and 2021. The results revealed that the highest food production (61.5 Mg ha−1) was recorded under M10 followed by M9 (59.9 Mg ha−1). Concerning environmental sustainability, the combination of crop + dairy + fishery + poultry + duckery + apiary + boundary plantation + biogas unit + vermicompost (M10) recorded considerably higher energy output (517.6 × 103 MJ ha−1), net energy gain (488.5 × 103 MJ ha−1), energy ratio (17.8), and energy profitability (16.8 MJ MJ−1) followed by M9. Furthermore, the M10 had the lowest greenhouse gas (GHG) intensity (0.164 kg CO2 eq per kg food production). However, M9 had the highest eco-efficiency index (44.1 INR per kg GHG emission) followed by M10. Hence, an appropriate combination of diversified and complementary enterprises in a form of IFS model is a productive and environmentally robust approach for sustainable food production in the northwestern part of India.